Social Ecology State of the Art and Future Prospects - Martin Zimmermann (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The book 'Social Ecology. State of the Art and Future Prospects' is published by ISOE - Institute for Social-Ecological Research, Frankfurt am Main and the Vienna Institute of Social Ecology (SEC). Both institutes have made defining contributions to the field of social ecology. How the complex relations between society and nature can be theoretically captured, empirically investigated and sustainably shaped is a focal question for both institutes. This book provides an overview of the current state of social-ecological research. It contains 11 contributions from 29 scientists, edited by Johanna Kramm and Martin Zimmermann (ISOE) and Melanie Pichler and Anke Schaffartzik (SEC). Topics range from the conceptional and theoretical foundations of social ecology to empirical case studies and research frontiers. The peer-reviewed essays highlight the role of social ecology as a critical, transdisciplinary science, discussing the current challenges for social-ecological transformations. Key concepts for sustainability research like ecosystem services, societal metabolism, risk, or extractive economies are applied and advanced.